Cointegrated VARMA models and forecasting US interest rates - Christian Kascha; Carsten Trenkler (University of Zurich, Department of Economics, 2011)
We bring together some recent advances in the literature on vector autoregressive moving-average models creating a relatively simple specification and estimation strategy for the cointegrated case. We show that in the cointegrated case with fixed initial values there exists a so-called final moving representation which is usually simpler but not as parsimonious than the usual Echelon form. Furthermore, we proof that our specification strategy is consistent also in the case of cointegrated series. In order to show the potential usefulness of the method, we apply it to US interest rates and find that it generates forecasts superior to methods which do not allow for moving-average terms.
Keywords: C32; C53; E43; E47; 330; Cointegration; VARMA Models; Forecasting; Kointegration; ARMA-Modell; Prognoseverfahren; Theorie